Semarang Business Incubator and Commercial Space Center with Sustainable Architecture Design - Rendi Noor Ilham; Wiwit Setyowati; Teguh Prihanto; Ardiyan Adhi Wibowo (Universitas Negeri Semarang, 2024)
Increasingly, Semarang City is experiencing significant MSME business growth. Judging from the economic, social, and environmental problems in this city, everyone is competing in advancing their region. With MSMEs, there are various entities that benefit, such as business owners and other people. These benefits can be in the form of financial benefits that can be a solution to problems in Semarang City, namely poverty and unemployment. The more income-generating entities, the faster economic problems are resolved. Therefore, a forum is needed that can be a place for business people, both old and new business people, to improve their therapy in business. The architectural planning and design program carried by the author is the design of